Peningkatan Kesehatan Gigi dan Mulut dengan Cara Kontrol Plak yang Benar pada Anak SDN Al Fityah Aceh Besar - RECA; Mufi Zarni; Eka Sri Rahayu (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Efforts to maintain dental and oral health should be carried out from this age. Elementary school age is an ideal time to train a child's motor skills, including brushing teeth. Good brushing habits must be formed at a young age because plaque control is very important for maintaining oral and dental health. In an initial survey conducted by 10 grade VI children at SDN AL-FITYAN Aceh Besar, it was found that 80% of children had poor OHIS criteria, which ranged from 1.9-3.0. The purpose of this activity is to increase knowledge about how to properly control plaque in SD AL-FITYAN Aceh Besar children and improve the dental and oral hygiene status of elementary school students. In this community service, dental and oral health improvement was carried out by correct plaque control for AL-FITYAN Aceh Besar elementary school children, using the Lecture, Question, and Answer, Demonstration, Discussion, and Simulation methods. The results of community service that have been carried out are an increase in student knowledge in maintaining oral and dental hygiene in AL-FITYAN SD Aceh Besar students, with an increase before the intervention (pre-test) in the poor category (66.7%) and after the intervention ( post-test) was in a good category (96.7%), There was an increase in the dental and oral hygiene status of SD AL-FITYAN Aceh Besar students, with an increase before the intervention (pre-test) in the very poor category (53.3%) and after the intervention (post-test) was in a good category (93.3%). It is recommended to the school to carry out counseling activities and brush teeth together regularly and involve parents, UKS teachers, and teachers to improve the dental and oral hygiene status of children. Keywords: Plaque, School Children, Dental Hygiene